Technical Assessment of Neuro-Symbolic AI for Cultural and Fractal Analysis of Batik Motifs - Rahmat Tullah; Lilis Stianingsih (UIN Sumatera Utara, 2025)
This study presents a structured literature review of Neuro-Symbolic Artificial Intelligence (NSAI) approaches for extracting cultural semantics and fractal features from Batik motifs. A structured multi-database screening (2015-2025) yielded 69 peer-reviewed studies, which were synthesized thematically. The review identifies three key findings: existing vision-based models generally lack explicit mechanisms for encoding intangible cultural rules; hybrid neural-symbolic approaches demonstrate improved interpretability and compositional reasoning; and fractal-based descriptors show promise for representing culturally grounded motif structures. Based on these findings, this study proposes a conceptual NSAI framework that combines symbolic knowledge representations with fractal feature modeling, without empirical validation at this stage. The synthesis highlights potential applications in motif recognition, generative motif modeling, and computer-assisted cultural heritage preservation. Overall, NSAI offers a feasible and explainable conceptual framework for modeling Batik's intangible cultural knowledge.